Telaah terhadap Undang-Undang Pornografi Perspektif Hukum Islam - Abdul Haris Abbas (Al-'Adl, 2017)
This paper reviews pornography laws in the study of Islamic law, even though their enactment has gained a lot of resistance and through a long process. From the review of Law no. 44 Year 2008 About Pornography, it is actually a formal and material element (legal material), has been very good and comprehensive enough to be used in preventing the occurrence of pornography and pornoaction, but in its implementation is still considered less effective because there are still some weaknesses both technical, Or juridical. Therefore it is necessary to propose to be revised in accordance with the findings in this paper.In the Qur'an requires thecreation of the benefit of the world and the hereafter for all humanity. Therefore, all manner of attitudes and actions that can lead a person to the destruction of human life are forbidden. Pornography and porno-action with its various forms are prohibited, such as adultery, opening aurat, saying or behaving in an arrogant manner expressly prohibited by Allah. Moreover, very negative impact because it can cause cases of rape, harassment, adultery, abortion, moral and moral damage, especially in children, and destroy the joints of community life, of course this is contrary to the objectives of Islamic law.